NIR‐II AIEgens for High‐Contrast Intravital Fluorescence Angiography: Recent Advances and Prospects - Zhijun Zhang; Xue Li; Hao Yang; Caifa You; Kui Ren; Zengming Yang; Miaomiao Kang; Dong Wang; Ben Zhong Tang (Aggregate)
ABSTRACT The vasculature, as the essential biological network for oxygen and nutrients delivery and the dynamic regulatory center for physiological processes, is fundamentally important for maintaining human health and life quality. Accurate visualization of vascular structures, as well as real‐time monitoring of hemodynamic parameters and molecular profiles associated with vascular function, are therefore crucial for early diagnosis and preventive interventions of vascular diseases. Fluorescence imaging technology, particularly in the second near‐infrared window (NIR‐II; 1000–1700 nm), offers distinct advantages for these demanding imaging requirements not only due to its high sensitivity, excellent spatial resolution, and real‐time monitoring capability but also thanks to the superior signal‐to‐background ratio and large tissue penetration depth of NIR‐II fluorescence. Among diverse NIR‐II fluorescent probes, aggregation‐induced emission luminogens (AIEgens) stand out for their intrinsic organic nature and, more importantly, for their unique aggregation‐enhanced emission properties, which clearly differentiates them from traditional fluorophores and enable high‐resolution imaging. Currently, a series of high‐performance NIR‐II AIEgens featuring relatively high fluorescence brightness and long emission wavelengths with emission tails even extending into the NIR‐IIa (1300–1400 nm) and NIR‐IIb (1500–1700 nm) subwindows have been reported and demonstrated encouraging results in intravital fluorescence angiography. This minireview summarizes recent advances in NIR‐II AIEgens for various vascular imaging applications, categorized by anatomical locations, including cerebral, abdominal, hindlimb, ear, axillary, renal, and tumor angiography. The molecular design strategies and nanoengineering approaches to achieve longer emission wavelengths, higher fluorescence brightness, and improved bioavailability are highlighted. Finally, the remaining challenges and future directions are discussed from the aspects of materials engineering, application scenarios expansion, and clinical translation.